HEAVY METALS AND AGRICULTURAL APTITUDE OF THE WATER IRRIGATION CHANNEL N RIVER LLALLIMAYO DISTRICT CUPI - Cano Ojeda, Julio Wilfredo (2022)
The research was carried out in the irrigation water Channel N located between the districts of Llalli and Cupi of the province of Medgar Puno region, at an altitude of 3950.00 m.s.n.m. East latitude 294,911,378 m. north 8343,943,106 m. irrigated by the waters of the Llallimayo river, with the objective of: evaluate water quality to verify the presence of heavy metals according to the Environmental Quality Standards category 3 D.S. 004-2017-MINAM and their suitability according to Riverside standards; by the constant socio-environmental conflicts raised in the basin, attributed to the activities carried out by the mining company Aruntani SAC. Six samples were collected, three upstream and three downstream of the Channel "N" irrigation distribution network, to evaluate the content of heavy metals and physicochemical parameters such as temperature, pH, electrical conductivity, ratio of absorption of sodium and residual sodium carbonate, applying the accredited Inductively Coupled Plasma Test Method (ICP-OES) for heavy metals, and qualify their ability to irrigate vegetables and animal drink according to ECA (Quality Standards) and Riverside Nomogram. None of the heavy metals exceeds ECA category 3 D1 and D2, therefore, it is suitable for irrigation and animal consumption; referring to T° 11.47, pH 8.29, CE. 0.423 mhos/cm, RAS 11.42 and CSR 2.42 qualifying as acceptable, S3 risky and not recommended respectively; According to the Riverside Nomogram (USDA) it qualifies as good quality water suitable for irrigation.